The 'tool box’ at states' disposal to prevent displacement: a Swiss perspective - Truedsson, I (Refugee Studies Centre, University of Oxford, 2012)
A harmful action that is looming and has not yet taken place is difficult for third-party states to denounce or counter. Nevertheless, a whole range of measures and methodologies is at their disposal enabling them to contribute to the prevention of forced displacement